Relatıons Between Cranıofacıal Structures And Farengeal Aırway Alteratıons After Bımaxıllary Surgıcal Procedures - Nazan Küçükkeleş; Tülin Arun; Sibel Biren; Sheraz Burki (Galenos Yayinevi, 1997)
Farengeal airway alterations are expecled after bimaxillary surgical procedures. (In the study bimaxillary surgery includes Le. Fort I osteotomy with maxillar intrusion and sagittal split osteotomy with mandibular set-bach), In order to evaluate the alterations due to the changes in craniofacial structure, one week preoperative and two months postoperative lateral cephalometric radiographs of 17 mandibular prognathic cases with high angle vertical pattern were used. The study was conducted an 17 patients (5 boys and 12 girls) whose chronologic mean age was 21.69±2.07 years. The findings were a constriction of nasofarengeal airway and an increase in the anteroposterior dimension of orofarengeal airway.